The modified age bracket of the Sangguniang Kabataan and its effect on the political attitudes of the youth - Aquino, Sheryl de Guzman; Martinez, Faith Theresa Dalaza (2003)
This study focused on the effects of the modified age bracket on the degree of political awareness as well as on the level of political participation of the respondents as manifestation of the political attitude of the youth. It seeks to determine whether or not the policy has an effect on the political attitude of the youth particularly on their political awareness and political participation. It aims to find out the level of awareness of the youth on political issues, the degree of the knowledge the youth have on governmental institutions and offices as well as on government activities and programs. Furthermore, this study will look at the reasons why registered Sangguniang Kabataan voted or did not vote during the July 15, 2003 Sangguniang Kabataan elections. In addition, it will look at the extent to which the youth participate and influence decision-making. This study believes that the modifies age bracket has significant effect on the political attitudes of the youth particularly on their degree of political awareness and level of political participation. It asserts that the youth are more likely aware to be of the political issues and are knowledgeable about governmental institutions and offices and governmental activities and programs. Lastly, this study maintains that the youth has high initiative on participating in political activities -- Author's abstract.